2014
DOI: 10.1186/1742-9994-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Host responses to interspecific brood parasitism: a by-product of adaptations to conspecific parasitism?

Abstract: BackgroundWhy have birds evolved the ability to reject eggs? Typically, foreign egg discrimination is interpreted as evidence that interspecific brood parasitism (IP) has selected for the host’s ability to recognize and eliminate foreign eggs. Fewer studies explore the alternative hypothesis that rejection of interspecific eggs is a by-product of host defenses, evolved against conspecific parasitism (CP). We performed a large scale study with replication across taxa (two congeneric Turdus thrushes), space (pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(132 citation statements)
references
References 77 publications
(188 reference statements)
2
126
4
Order By: Relevance
“…Third, a host species may reject relatively nonmimetic eggs, but this may just be a by-product of adaptations that evolved in the context of conspecific parasitism (López-de-Hierro and Moreno-Rueda 2010; Samas et al 2014), although this latter problem is unlikely to be important in the present study species (Kempenaers et al 1995;review in Griffith et al 2002). Fourth, experimental nests may be deserted not because of the introduction of experimental eggs but due to any unrelated disturbance; therefore, it is necessary to use control (unmanipulated) nests to determine whether desertion represents a specific response to parasitism (Samas et al 2014). For these reasons, it is necessary to use conspecific, mimetic and nonmimetic experimental eggs and control nests to reveal both host egg discrimination ability and the evolutionary origin of this ability (Grim 2005).…”
Section: Egg Experimentscontrasting
confidence: 44%
See 2 more Smart Citations
“…Third, a host species may reject relatively nonmimetic eggs, but this may just be a by-product of adaptations that evolved in the context of conspecific parasitism (López-de-Hierro and Moreno-Rueda 2010; Samas et al 2014), although this latter problem is unlikely to be important in the present study species (Kempenaers et al 1995;review in Griffith et al 2002). Fourth, experimental nests may be deserted not because of the introduction of experimental eggs but due to any unrelated disturbance; therefore, it is necessary to use control (unmanipulated) nests to determine whether desertion represents a specific response to parasitism (Samas et al 2014). For these reasons, it is necessary to use conspecific, mimetic and nonmimetic experimental eggs and control nests to reveal both host egg discrimination ability and the evolutionary origin of this ability (Grim 2005).…”
Section: Egg Experimentscontrasting
confidence: 44%
“…This is most likely because we used standard tit nest boxes with small entrances (entrance diameter = 3.5 cm). Although cuckoo females are able to squirt the egg even into small entrance cavities (Davies 2000), such layings cannot establish a viable cuckoo gens (host race)-cuckoo chicks would not fledge from a small entrance cavity and the strain would go extinct in the very first generation (see also Grim et al 2011;Samas et al 2014). Therefore, a cuckoo gens specialized on parasitizing tits (or any other bird species) breeding in small cavities (natural or artificial) cannot exist in principle.…”
Section: Aq8mentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of European thrushes (genus Turdus) reject foreign eggs, yet the evolutionary causes of this behavior remained unclear. Recently, we concluded that conspecific (CBP), rather than interspecific brood parasitism (IBP) is responsible for the patterns of foreign egg rejection in these taxa [1]. In his comment M. Soler does not agree with this conclusion.…”
mentioning
confidence: 48%
“…Although the tendency is to often assume that interspecific parasitism is the evolutionary driver of host traits, perhaps because interspecific parasitism is often more obvious and easily detected than conspecific parasitism, it is possible that some signatures of coevolution might instead be fuelled by the brood parasitism within the hosts themselves (Freeman, 1988;Lahti, 2006;Lyon and Eadie, 2004). In these taxa it has proven difficult to disentangle the relative roles of conspecific and interspecific brood parasitism as drivers of host defenses (Freeman, 1988;Grendstad et al, 1999;Jackson, 1992;Lahti, 2006;Peer et al, 2007;Rothstein, 2001;Samas et al, 2014). However, one potentially powerful method for distinguishing between conspecific and interspecific interactions as the agent of selection is a geographical comparison of egg rejection behavior in regions where hosts are sympatric versus allopatric with their interspecific brood parasites (Lahti, 2006).…”
mentioning
confidence: 99%